Bleeding management for pediatric craniotomies and craniofacial surgery. Issue 7 (12th May 2014) - Goobie, Susan M.; Haas, Thorsten; Soriano, Sulpicio
Summary Pediatric patients when undergoing craniotomies and craniofacial surgery may potentially have significant blood loss. The amount and extent will be dictated by the nature of the surgical procedure, the proximity to major blood vessels, and the age, and weight of the patient. The goals should be to maintain hemodynamic stability and oxygen carrying capacity and to prevent and treat hyperfibrinolysis and dilutional coagulopathy. Over transfusion and transfusion‐related side effects should be minimized. This article will highlight the pertinent considerations for managing massive blood loss in pediatric patients undergoing craniotomies and craniofacial surgery. North American and European guidelines for intraoperative administration of fluid and blood products will be discussed.